Myasthenia gravis complicated with pulmonary infection by Nocardia cyriacigeorgica: a case report and literature review - Zuo, Huifen; Ye, Jiaqing; Li, Chenfei; Li, Shijie; Gu, Jingxin; Dong, Na; Zhao, Yihan; Hao, Jiahao; Song, Minghui; Guo, Yumei; Gao, Weili; Zhao, Zhenjun; et al. (Frontiers in Medicine, 2024)
Myasthenia gravis (MG) is an autoimmune disease. Patients with MG due to compromised autoimmune regulation, progressive muscle weakness, and prolonged use of immunosuppressants and glucocorticoid, often present with concomitant infections. However, cases of MG complicated by Nocardia infection are rare. In this case, we report MG complicated with pulmonary infection by Nocardia cyriacigeorgica. A 71-year-old male farmer who was admitted for management of MG. After 7 weeks of treatment of MG, the patient reported improvement. However, clinical presentation, inflammatory markers, and imaging findings supported a diagnosis of pulmonary infection. To further elucidate the etiology, Nocardia was identified in sputum smear microscopy and sputum culture, with 16S rRNA gene sequencing confirming N. cyriacigeorgica. The patient was prescribed trimethoprim-sulfamethoxazole. After 1 month of treatment, clinical symptoms of MG and pulmonary nocardiosis showed significant improvement. Additionally, we searched PubMed for case reports of Nocardia cyriacigeorgica pulmonary infection from 2010 to 2024 and conducted a statistical analysis of the case information. This report aims to highlights the increased risk of pulmonary Nocardia infection in MG patients after the use of steroids and immunosuppressants, thereby enhancing clinical awareness.